The Potential Postharvest Treatments to Delay Flower Senescence and Improve Botrytis Resistance in Cut Peony Flowers - Toan Nguyen; Suong Ha (Horticulturae)
The herbaceous peony (Paeonia lactiflora Pall.) flower is one of the most important ornamental plants in current international flower markets and is widely used for festive occasions because of its bright colors, large flowers, pleasant scent, and plump flower shape. However, the cut peony flowers have a relatively short postharvest life in vases compared to other flower species. The short vase life and susceptibility to gray mold disease caused by Botrytis cinerea significantly influence the commercial value of cut peonies. Here, we reviewed the main factors for postharvest quality reduction in cut peony flowers and the various postharvest treatments aiming for vase life extension and enhancing gray mold disease resistance in cut peonies. Chemical treatments, including ethylene inhibitors, antimicrobial agents, and other preservatives, have been assessed for their effectiveness in improving vase life. Moreover, physical treatments, such as temperature management, controlled atmosphere storage, and dry storage methods, were also discussed for their effectiveness in delaying flower senescence and reducing gray mold disease infection. The review also highlighted the importance of cultivar-specific responses to gray mold disease, ethylene, and water stress, which is important for the development of new effective and specific postharvest practices to improve the vase life of cut peonies.